Kualitas Pelayanan Kesehatan di Puskesmas Ngaliyan Kota Semarang - Lita Listyoningrum; Ida Hayu Dwimawanti; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Quality is a condition that shows conformity between expected with the reality both in the individual and group .Health services is any effort that held in its own or together in an organization to maintain and improve health, prevent and treat disease and restore the health of individual and group.Puskesmas ngaliyan is one of the organizers of the organization of the government health service in semarang city. This research aims to know about the quality of health services at puskesmas ngaliyan semarang city as well as the bottleneck supporters and the quality of health services at puskesmas Ngaliyan. Based on research results can be concluded that the quality of health services in puskesmas ngaliyan not yet done well .This can be seen from five dimensions the quality of service , namely: Tangibles , realibility , responsivness, Assurance and emphaty .Faktor that inhibits and support the quality of service; customers , the strategy , the sistem , human resources .Based on the results of research , the researchers recommend to the officers puskesmas ngaliyan semarang city to fix some indicators and the factors considered still not optimal.